Population attributable fraction of risk factors for anemia among children aged 6–59 months: A multilevel complex data analysis using modified poisson regression model in Sub-Saharan Africa - Meklit Melaku Bezie; Beminate Lemma Seifu; Hiwot Altaye Asebe; Angwach Abrham Asnake; Yohannes Mekuria Negussie; Zufan Alamrie Asmare; Mamaru Melkam; Bezawit Melak Fente (PLoS ONE, 2025)
Background Anemia among children under five remains a significant public health concern in sub-Saharan Africa (SSA). While numerous studies have examined its associated factors, limited evidence exists on the public health impact of modifiable risk factors. This study assessed the population-attributable fraction (PAF) of risk factors for anemia among children aged 6–59 months across 27 SSA countries. Methods A secondary data analysis was conducted using Demographic and Health Survey (DHS) data from 27 SSA countries, including a weighted sample of 124,285 children. Data management and analysis were done using STATA-14 software. The presence of clustering was assessed using the Intra-cluster Correlation Coefficient (ICC), Median Odds Ratio (MOR), and Likelihood Ratio Test (LRT). A multilevel modified Poisson regression model was employed to estimate adjusted Prevalence Odds Ratios (aPOR) and the corresponding PAF with 95% Confidence Intervals (CI), and the Population Attributable Fraction (PAF) with the 95% CI was estimated using the aPOR and the prevalence of exposure. Results The overall prevalence of anemia among children in SSA was 61.99% (95% CI: 61.73, 62.27). Significant risk factors included maternal anemia (PAF = 7.37%), low maternal education (PAF = 5.86% for no formal education), poor household wealth status (PAF = 3.52% for the poorest), lack of media exposure (PAF = 0.76%), child undernutrition (stunting PAF = 1.31%, underweight PAF = 0.84%), diarrheal (PAF = 1.19%) and febrile illness (PAF = 2.26%), and unimproved toilet facilities (PAF = 1.02%). Conclusion Maternal anemia, low maternal educational status, poverty, poor sanitation, inadequate media access, unimproved toilet facilities, and childhood illness significantly contribute to anemia in SSA. Targeted interventions to improve maternal and child health, enhance education, and ensure better nutrition and sanitation could help reduce childhood anemia in the region.